RELEVANSI HIRARKI LIMA KEBUTUHAN DASAR MASLOW DAN Al-SYATIBI DAN PENERAPANNYA DALAM TRIPUSAT PENDIDIKAN - Muhammad Al Mighwar; H. Ahmad Maki; Muhammad Saleh Suhaidy; Huges; Fahrizal Akhirudin (al-Afkar, Journal For Islamic Studies, 2022)
THE RELEVANCE OF THE HIERARCHY OF FIVE NEEDS OF MASLOW AND SYATIBI AND ITS APPLICATIONS IN EDUCATIONAL FAMILY This study aims to determine the relevance of Maslow and Syatibi's five hierarchy of basic needs and their application in education Tricenter. The research approach is qualitative with a literature review method where data collection is carried out through reviewing various primary and secondary book and journal literatures as well as daily experiences, then analyzed using the Miles and Huberman interactive data analysis technique, namely data collection, data reduction, data exposure, and conclusion. This study found that: (1) Maslow and Syatibi's hierarchy of five basic needs has a meeting point in the aspect of the category of importance, substance, and benefit for all humans; and (2) the relevance of Maslow's and Syatibi's five basic needs hierarchy can be integrated in their application in a plural/plural education Tricenter in the same way (adoption) or complement each other and develop it (adaptation) according to their respective conditions as long as they fulfill the five elements of the participants' basic needs. educate and support / ensure the growth and development of its potential.